The relationship between innovativeness, export capability and business performance of companies - Šlogar, Helena (Oeconomica Jadertina, 2021)
The necessity of an accelerated economic growth has spurred the researchers’ interest in the relationship among innovativeness and export capability and business performance of companies. The situation in the Croatian economy is highly complex, exhibiting a low growth level of GDP, foreign trade deficit and high external debt. The situation requires major changes in the economic policy of the Republic of Croatia, particularly since foreign trade is an important factor of the economic development of the country and the increase in export capability of Croatian companies is one of the major determinants of a long-term economic growth. Bearing this in mind, scientists have developed a common interest to research the impact of innovativeness, in particular its dimensions regarding the increase in export capability and business performance of companies. The objective of this paper is to examine whether the model of relationship between innovativeness, its dimensions, export capability and business performance in Croatian companies ever changed in the period from 2016-2019. The covariance and regression analyses were performed to analyse the data. The results show that no statistically significant difference existed between innovativeness and exports either in 2016 or in 2019, and these findings have theoretical and practical implications.